The Effect of Nutrition Status and Occupancy Density Compliance with Home Contact Pulmonary TB Insidence in Specialized Hospital of Pulmonary - Dahwan, Dahwan; Aguslina, Fazidah; Hasan, Wirsal (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Pulmonary Tuberculosis is an important and serious public health problem throughout the world. It is caused by Mycobacterium tuberculosis which attacks lungs and other body organs. This study aimed to determine the effects of nutritional status and dwelling density on the risk of pulmonary TB incidence in Medan, North Sumatera. This was a case control study conducted at Pulmonary Disease Hospital, Medan, North Sumatera, from January to June in 2018. A sample of 120 patients was selected for this study, consisting 60 patients with TB and 60 patients without TB. The dependent variable was TB incidence. Data were collected through observations and interviews using questionnaires. Data was analyzed by bivariate using simple logistic regression test and multivariate by multiple logistic regression. The result showed poor nutritional status is closely associated with pulmonary TB infection. Impact of nutritional status and occupancy density on incidence of Pulmonary contact TB at Median Specialized Hospital in 2018.